Influence of comorbid anxiety and depression disorder on cognition in older adults with epilepsy - Qiu, Hui; Wang, Zongqin; Wang, Yanyan (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to investigate the association of comorbid depression and anxiety with cognitive function in older adults with epilepsy.MethodsA cross-sectional analysis was conducted on 406 older adults (≥65 years) diagnosed with epilepsy between January 2019 and December 2020. Depressive and anxious symptoms were measured using the Hospital Anxiety and Depression Scale (HADS), while cognitive impairment was assessed with the Montreal Cognitive Assessment Test (MoCA). Multivariate linear regression models were used to examine associations between cognitive impairment and anxiety/depression symptoms, adjusting for potential confounders.ResultsOf the 406 adults, 218 (53.7%) showed cognitive impairment. Adults with depression (70.2% vs. 51.0%, P<0.01) or anxiety (66.7% vs. 48.8%, P<0.01) had a significantly higher prevalence of cognitive impairment compared to those without these conditions. Multivariate linear regression analysis revealed significant associations between cognitive impairment and depression (β=-1.77, 95% CI: -2.67, -0.87; P<0.01) and anxiety (β=-2.18, 95% CI: -2.95, -1.42; P<0.01).ConclusionAnxiety and depression are significantly associated with cognitive impairment in older adults with epilepsy. Early screening and management of these psychiatric conditions are essential to reduce cognitive decline and enhance patient outcomes.